Graft-versus-host Disease Prophylaxis With Abatacept Reduces Severe Acute Graft-versus-host Disease in Allogeneic Hematopoietic Stem Cell Transplant for Beta-thalassemia Major With Busulfan, Fludarabine, and Thiotepa. Issue 4 (25th May 2020) - Khandelwal, Pooja; Yeh, Rosa F.; Yu, Louie; Lane, Adam; Dandoy, Christopher E.; El-Bietar, Javier; Davies, Stella M.; Grimley, Michael S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: We hypothesized that the addition of 4 doses of abatacept to our standard acute graft-versus-host disease (GVHD) prophylaxis would reduce the incidence of day +100 severe acute GVHD in children with transfusion-dependent beta-thalassemia major undergoing a myeloablative allogeneic hematopoietic stem cell transplant (HSCT), without impacting engraftment. Methods: Twenty-four children with beta-thalassemia major received abatacept at a dose of 10 mg/kg intravenously on days –1, +5, +14, and +28 after HSCT in addition to calcineurin inhibitors and methylprednisolone. Outcomes were compared to 8 beta-thalassemia patients who received standard acute GVHD prophylaxis. Results: There was no difference in engraftment between the 2 groups. No patient had grades III–IV acute GVHD by day +100 in the abatacept cohort compared with 50% in the standard acute GVHD prophylaxis group ( P = 0.001). Viral reactivation occurred in 5 children in the standard acute GVHD cohort and in 20 children in the abatacept cohort ( P = 0.2). Thalassemia-free survival after HSCT was 100% in the abatacept cohort compared to 62.5% in the standard cohort at last follow-up ( P = 0.007). Conclusions: Adding abatacept to our routine GVHD prophylaxis reduced the incidence of day +100 severe acute GVHD without impacting engraftment or survival.